1983
DOI: 10.1136/jcp.36.10.1188
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histological assessment of hepatic lipid in sudden infant death syndrome.

Abstract: YorkshireSUMMARY A biochemical and histological study of hepatic lipid in children dying from the sudden infant death syndrome (SIDS) and children of a similar age dying explicably are reported. Contrary to a previous report based on histological assessment of hepatic lipid, no significant increase of total lipid content in livers of children dying from SIDS was found. Analysis of hepatic phospholipid fatty acid esters, however, revealed a significant difference between SIDS and children of similar age dying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…This was significant (P<.05) for hepatic TG only (Table 4). Coincidently, these observations parallel reports on hepatic (Cairns et al, 1983) and lung surfactant (Morley et al, 1982) lipid composition in infants dying from Sudden Infant Death Syndrome (SIDS). Based on the findings of investigations of SIDS, it has been suggested that increased desaturation of membrane lipids as reflected by the DBI/SFA increases membrane fluidity and disrupts the activity of membrane bound enzymes (Cairns et al, 1983).…”
Section: Resultssupporting
confidence: 66%
“…This was significant (P<.05) for hepatic TG only (Table 4). Coincidently, these observations parallel reports on hepatic (Cairns et al, 1983) and lung surfactant (Morley et al, 1982) lipid composition in infants dying from Sudden Infant Death Syndrome (SIDS). Based on the findings of investigations of SIDS, it has been suggested that increased desaturation of membrane lipids as reflected by the DBI/SFA increases membrane fluidity and disrupts the activity of membrane bound enzymes (Cairns et al, 1983).…”
Section: Resultssupporting
confidence: 66%